The effect of population growth on the agricultural production in Nigeria : (1961-2013) - Aina, Ifedotun Victor (Array, 2019)
As of 2000, the total population estimate of Nigeria stood at about 124 million people, this number increased to 170 million in the year 2012, which shows a growth rate of 3.8% between 2000 and 2012. This figure provides an indication that the Nigerian population is among the fastest-growing populations in the world, on the other hand, food production increases marginally, at a rate lower than the population growth rate. This paper examined the effect of the Nigerian population on agricultural production over a period of 53 years. Descriptive analysis was used to analyse the pattern and the trend of agricultural production. Granger causality and Ordinary Least Squares were used to examine the relationship between agricultural production and population growth. It was recommended that there is a need for the government to support innovative ways for increasing agricultural production, to meet the demand of the increasing population of the country. There is a need for research bodies to improve production to match the country’s increasing population, so sustainable development could be achieved. In order for agricultural production to meet the increasing population demand, there is a need for the development of improved high-yield, disease-resistant varieties coming from certified nurseries where the varieties can be traced. There is a need for innovative processes through which agricultural products and processing methods can be learned through extension services by the general population, so as to reduce malnutrition and poverty in the country.